Dissolved organic carbon concentration and its relationship to electrical conductivity in the waters of a stream in a forested Amazonian blackwater catchment - Monteiro, Maria Terezinha F.; Oliveira, Sylvia Mota de; Luizão, Flávio Jesus; Cândido, Luiz Antônio; Ishida, Francoise Yoko; Tomasella, J. (Plant Ecology and Diversity, 2014)
Background: Dissolved organic carbon (DOC) is a major component of the total carbon in headstreams in Amazonia. Long-term measurements of DOC concentration are difficult to obtain in remote areas of Amazonia. Aims: To take measurements of electrical conductivity (EC) and DOC concentration in a blackwater stream and to determine whether it is possible to make predictions of the DOC concentration in such streams using continuous measurements of EC alone. Methods: In a forested area, DOC concentration and EC were measured in groundwater along a topographic gradient at weekly intervals over a period of 8 months, and in stream water at half-hourly intervals over 2 years. Results: Strong and positive relationships between EC and DOC concentration were found in stream water in wet (r 2 = 0.99) and dry periods (r 2 = 0.97). It was thus possible to produce two equations that could be used to derive DOC concentration values from continuous measurements of EC. Both DOC concentration and EC varied according to the discharge, indicating that the largest amounts of DOC are transported during the wet season. The amount of carbon exported annually was estimated to be between 2.5% and 5% of the sink estimated by the eddy covariance method. Conclusions: The relationship found offers an opportunity for a comprehensive assessment of DOC concentration in blackwater catchments based on low-cost and simple EC measurements, rather than on expensive and complex estimates of DOC concentration. © 2014 Copyright 2013 Botanical Society of Scotland and Taylor & Francis.